Optimalisasi Potensi Industri Halal di Indonesia Melalui Peran Pasar Modal Syariah - Melisa; Lailatul Khikmawati (Al-Iqtishod : Jurnal Ekonomi Syariah, 2021)
The halal trend in Indonesia is increasingly in demand by the public. The potential of the halal industry in Indonesia is also growing rapidly. These industries include food and beverages, fashion trends, and halal tourism. The industrial development is increasingly visible and points to a better direction for economic development in Indonesia. However, usually in terms of funding the halal industry often experiences problems. The purpose of this research is to optimize the potential for the development of the halal industry in Indonesia through funding by the Islamic capital market. IDX works together with the OJK to make it easier for halal industry players to enter the Islamic capital market with various forms of funding products that are being developed, namely IPO, sukuk, and ECF.